Hacking the hackers. (Economist, 2015)
The article focuses on the French computer security company Cryptosense, which has created an automated system that alerts users to vulnerabilities through penetration testing. Topics include how the program finds problems in existing software and the concept of automatic hacking, in which the computer detects security issues on its own software.